05 Just saying 'No'? factors associated with patients' non-acceptance of ambulance transport against clinicians' advice. Issue 3 (1st March 2011) - Thompson, Fiona; Jacob, Rebecca; Watson, Peter; Holland, Anthony; Clare, Isabel
Abstract : Introduction: While studies in the United States have found great variation (from 2–30% of responses) in the prevalence of patients declining transport by ambulance to hospital against the advice of the treating clinicians, there is agreement that an estimated 1% have a serious medical complaint. Management of such patients poses significant medical, legal and ethical dilemmas for frontline staff. Aim: The aim of our study was to ascertain the prevalence of patients who do not accept transport to hospital by ambulance and to identify clinical and demographic factors associated with this group. We hypothesised that a proportion of these patients would present with problems that may be associated with diminished decision-making capacity. Method: Patient Report Forms from all ambulance responses (total 7309) over three counties in the East of England over 2 weeks were reviewed. Patients who had declined transport, clearly contrary to the advice of the treating staff, were identified and clinical and demographic data collected and compared with controls who had accepted transport. Results: One hundred and fifteen responses, making up almost 2% of all responses by the ambulance service, resulted in the patient declining transport to hospital against the advice of treating staff. These patients were more likely to be male, less than forty years old and living alone. Mental health problems including self-harm, suicidal ideation and intoxication with substances were more prevalent in the non-acceptors. Medical complaints prevalent in the non-acceptors included altered level of consciousness, confusion, diabetes, head injury, overdose and seizures. Conclusion: Patients declining transport presented with conditions that are potentially associated with a disability of brain or mind and might, therefore, affect decision-making capacity. Consistent national guidelines, along with training and support of frontline staff are required to ensure optimal care of patients declining transport to hospital, a proportion of whom may be lacking the capacity to make decisions about transport.